An integrative review on treatment guidelines for complicated urinary tract infections: a synthesis of evidence-based recommendations - Bittencourt, Amanda Azevedo (2025)
Urinary tract infections (UTI) lie among the most common bacterial infections worldwide. Since their manifestations can range from laboratory findings (asymptomatic bacteriuria) to septic shock, using appropriate antimicrobial agents is crucial to avoid complications and the misuse of antibiotics. This study aims to review scientific publications and the main guidelines to treat complicated UTI. A literature review was carried out in September 2022 on the LILACS, MEDLINE via PubMed, and SciELO databases. Descriptors, keywords, and MeSH terms were used to develop search strategies. Full documentation meeting the following criteria was included: management of patients with a diagnosis of complicated UTI; guidelines, recommendations, consensus articles, expert opinion articles (with recommendations), and meta-analyses including data from randomized controlled trials; and articles published from 2001 to 2022. Articles published in languages other than English, Spanish, French, and Portuguese and those unrelated to complicated UTI were excluded. After applying the eligibility criteria, 28 studies were included in this review. Fluoroquinolones are the most frequently recommended option for complicated cystitis and pyelonephritis. Guideline recommendations for recurrent UTI include antibiotic prophylaxis and treatment. Guidelines developed to propose treatment strategies for the pediatric population typically stratify cases according to their infection site (upper or lower),and the presence of fever. Guidelines propose different approaches, likely related to local antibiotic resistance and varying clinical manifestations. In this context, antimicrobial stewardship practices are essential to promote the adequate use of antibiotics for complicated UTI and to avoid antimicrobial resistance.